Assessing Stock Return: Findings from Consumer Goods Industry in Indonesia - Fitria Mandaraira; Said Muniruddin (IAIN Langsa, 2016)
This study aims to determine the impact of earnings per share (EPS), dividendpayout ratio (DPR), debt to equity ratio (DER), and investment opportunity set(IOS) on stock return. Population of this study is consumer goods industry sectorcompanies listed on Indonesia Stock Exchange (IDX). The total sample wastaken compromising 17 companies within a period from 2010-2013, by usingpurposive sampling method. The data used are secondary data and analyticalmethods use is regression analysis test tools. The results of this study showedthat there are no impacts of earnings per share, dividend payout ratio, debt toequity ratio, and investment opportunity set partially and simultaneously on stockreturn on the consumer goods industry sector companies. The results of thisstudy mostly influenced by the performance of consumer goods industry sectorcompanies that have high stability and resistant towards crisis.